BK CAREER IN HIGH SCHOOL (SMA & SMK) - Sambas Sugiarto; Daharnis; Mega Iswari (Yayasan Citra Dharma Cindekia, 2021)
Education is very important in determining a career in Indonesia. The main thing in career guidance activities in high school for various individuals must be based on the intensity of planning, the readiness to participate in life as an independent person, and the direction of the individuals towards their goals. By having various characteristics, plans to achieve career goals and students develop an awareness of the need for more specific implementation of career goals. Then develop and implement plans to meet the entry requirements for employment by taking courses at the secondary school level, by in-service training, or by pursuing further training in college or post-secondary education leading to qualifications for a special occupation.